2021
DOI: 10.1002/adom.202001171
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexing Liquid Biopsy with Surface‐Enhanced Raman Scattering Spectroscopy

Abstract: Among the main challenges faced in cancer research, early detection, metastatic pathways and biomarker discovery are being tackled both by researchers and technology‐based companies. The development of novel technologies that can advance the state‐of‐the‐art for those defined challenges is critical in order to enhance the survival rates as well as to significantly lower cancer associated costs, not to mention social and human impact. In the recent years, the field of liquid biopsy has grown tremendously due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 203 publications
(188 reference statements)
0
9
0
Order By: Relevance
“…On the one hand, previous works benefiting from microdroplets technology for the imaging of single cells have been mostly focused on the use of fluorescence imaging, limiting the number of biomarkers that can be studied at the same time. [67,68] On the other hand, SERS imaging of cells based on protein expression has been reported. For example, Nima et al demonstrated the analysis of the pheno type of CTCs using this strategy, but in a bulk experiment ) SERS spectra acquired at the surface of each of the five single-cells displayed in (a) after labeling with GNSs@1-NAT@SiO 2 @EpCAM.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, previous works benefiting from microdroplets technology for the imaging of single cells have been mostly focused on the use of fluorescence imaging, limiting the number of biomarkers that can be studied at the same time. [67,68] On the other hand, SERS imaging of cells based on protein expression has been reported. For example, Nima et al demonstrated the analysis of the pheno type of CTCs using this strategy, but in a bulk experiment ) SERS spectra acquired at the surface of each of the five single-cells displayed in (a) after labeling with GNSs@1-NAT@SiO 2 @EpCAM.…”
Section: Discussionmentioning
confidence: 99%
“…[157] Recent advances in nanofabrication of homogeneous SERS substrates, combined with development within user-friendly and compact miniaturized systems could advance SERS substrates toward clinical implementation. [152] www.advancedsciencenews.com www.small-journal.com…”
Section: Surface-enhanced Raman Scattering (Sers)mentioning
confidence: 99%
“…Currently, only a limited number of SERS‐based ctDNA detection methods have been reported [ 152 ] and fully portable ctDNA‐based SERS platforms are yet to be realized. However, efforts toward portable platforms have been reported.…”
Section: Micro and Nano Biosensors For Liquid Biopsymentioning
confidence: 99%
“…Microfluidics has been coupled with a broad range of sensing technologies such as fluorescence, mass-spectrometry, electrochemistry, and UV–vis. , The diversity of applications arising from these combinations in the context of cancer covers not only diagnostics but also treatment, drug development and dosing, single-cell and genetic material analysis, and organ-on-a-chip applications. In line with these developments, optofluidic SERS platforms are being increasingly explored in biosensing . Label-free SERS measurements in microfluidic platforms have demonstrated remarkable performance for a broad range of biological targets such as bacteria, DNA, miRNA, narcotics, and food contaminants. Very recently, with the advent of personalized medicine and the revolution in data analytics, new opportunities to boost SERS-on-a-chip technologies are being explored. …”
Section: Label-free Sers Cancer Diagnosis On Chipmentioning
confidence: 99%